2014
DOI: 10.1186/1471-2474-15-359
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain among school teachers in Botswana, prevalence and risk factors

Abstract: BackgroundAlthough low back pain (LBP) represents a common occupational problem, few epidemiological studies have investigated the prevalence and risk factors for LBP among school teachers, particularly in Africa. School teachers are known to represent an occupational group among which there appears to be a high prevalence of LBP. The objective of this study was, therefore, to conduct one of the first epidemiological investigations of LBP among teachers in Botswana.MethodsA cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
104
3
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(134 citation statements)
references
References 39 publications
18
104
3
9
Order By: Relevance
“…5 This study has revealed that female 78% and male 57.5% reported with the prevalence of LBP. Low back problem in the current study was more than that in Saudi 63.8%, 9 Botswana 55.7%, 14 Turkish teachers 74.9%, 11 Iranian teachers in a previous study 39 and in another Turkish study 51.4%, 31 China 40.0%, 26 France 34.8% 34 and Japan 20.6%. 43 The results of this part of study were relatively lower than Slovenian physical education 84.0%.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…5 This study has revealed that female 78% and male 57.5% reported with the prevalence of LBP. Low back problem in the current study was more than that in Saudi 63.8%, 9 Botswana 55.7%, 14 Turkish teachers 74.9%, 11 Iranian teachers in a previous study 39 and in another Turkish study 51.4%, 31 China 40.0%, 26 France 34.8% 34 and Japan 20.6%. 43 The results of this part of study were relatively lower than Slovenian physical education 84.0%.…”
Section: Discussionmentioning
confidence: 75%
“…The findings of this study showed that 78% of the teachers reported prevalence of LBP. Results of this part of the current study are more than some developing countries such as Filipino 53.3%, 3 Botswana 55.7% 14 and Ethiopian 53.8%. 5 This study has revealed that female 78% and male 57.5% reported with the prevalence of LBP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…La survenue des ATL chez les sujets relativement âgés a été expliquée par la modification de la structure et des capacités fonctionnelles du disque intervertébral ainsi que par la diminution progressive de la masse musculaire lombaire et la perte d'élasticité tissulaire avec l'âge (17). Par ailleurs, la prédominance masculine a été attribuée en partie à la nature des tâches exigeant une force musculaire, habituellement confiées aux hommes.…”
Section: Discussionunclassified
“…Кроме того, исследования также показали, что профессиональные факторы связаны с развитием БНЧС [28][29][30]. Было отме-чено, что сидячие или офисные работники в школах, больницах и вооруженных силах имеют высокую распро-страненность БНЧС [31][32][33].…”
unclassified